Cost-effectiveness of computerized cognitive–behavioural therapy for the treatment of depression in primary care: findings from the Randomised Evaluation of the Effectiveness and Acceptability of Computerised Therapy (REEACT) trial. Issue 10 (23rd February 2017) - Duarte, A.; Walker, S.; Littlewood, E.; Brabyn, S.; Hewitt, C.; Gilbody, S.; Palmer, S.
Abstract : Background: Computerized cognitive–behavioural therapy (cCBT) forms a core component of stepped psychological care for depression. Existing evidence for cCBT has been informed by developer-led trials. This is the first study based on a large independent pragmatic trial to assess the cost-effectiveness of cCBT as an adjunct to usual general practitioner (GP) care compared with usual GP care alone and to establish the differential cost-effectiveness of a free-to-use cCBT programme (MoodGYM) in comparison with a commercial programme (Beating the Blues) in primary care. Method: Costs were estimated from a healthcare perspective and outcomes measured using quality-adjusted life years (QALYs) over 2 years. The incremental cost-effectiveness of each cCBT programme was compared with usual GP care. Uncertainty was estimated using probabilistic sensitivity analysis and scenario analyses were performed to assess the robustness of results. Results: Neither cCBT programme was found to be cost-effective compared with usual GP care alone. At a £20 000 per QALY threshold, usual GP care alone had the highest probability of being cost-effective (0.55) followed by MoodGYM (0.42) and Beating the Blues (0.04). Usual GP care alone was also the cost-effective intervention in the majority of scenario analyses. However, the magnitude of the differences in costs and QALYs between all groups appeared minor (and non-significant). Conclusions: Technically supported cCBT programmes do not appear any more cost-effective than usual GP care alone. No cost-effective advantage of the commercially developed cCBT programme was evident compared with the free-to-use cCBT programme. Current UK practice recommendations for cCBT may need to be reconsidered in the light of the results.